Optimization of Work Systems and Ergonomics to Improve Comfort and Efficiency Through The Implementation of Energy Management - Widyasmoro, Adi; Agustin, Silvi; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (International Journal of Business, Law, and Education, 2024)
This research aims to implement mall operations that are comfortable, efficient, and effective in energy use and determine the value of Energy Consumption Intensity (IKE). This research uses a qualitative method with a literature study approach. Research data was obtained from measurements carried out by researchers at mall buildings in South Jakarta. Instrument data is obtained from the installed Kwh meter. Data analysis technique by comparing measurement results with data results standardized by the Ministry of Energy and Mineral Resources for IKE and Indonesian National Standards for thermal comfort levels. The research results obtained show that the IKE value is classified as efficient. The IKE value during 2023 ranges from 8,79 – 11,37 kWh/m2/month with the total annual IKE value being 263,16 kWh/m2/year. In terms of air conditioning, the average comfort standard in 2023 will be 25℃ and RH (humidity) at 62.9%.